2019
DOI: 10.3389/fpls.2019.00480
|View full text |Cite
|
Sign up to set email alerts
|

The Strawberry FaWRKY1 Transcription Factor Negatively Regulates Resistance to Colletotrichum acutatum in Fruit Upon Infection

Abstract: Strawberry ( Fragaria × ananassa ) is a major food crop worldwide, due to the flavor, aroma and health benefits of the fruit, but its productivity and quality are seriously limited by a large variety of phytopathogens, including Colletotrichum spp. So far, key factors regulating strawberry immune response remain unknown. The FaWRKY1 gene has been previously proposed as an important element mediating defense responses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 73 publications
2
24
0
Order By: Relevance
“…A total of 58 PpWRKY genes have been identified in the genome of Prunus persica [16]. WRKY proteins have been verified to be essential in the defense response to various biotic and abiotic stresses, including low or high temperature, mechanical damage, and pathogenic infection [17,18,19,20,21,22,23]. In addition, there is a great deal of definite evidence indicating that the regulation of plant development and metabolism also requires WRKYs.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 58 PpWRKY genes have been identified in the genome of Prunus persica [16]. WRKY proteins have been verified to be essential in the defense response to various biotic and abiotic stresses, including low or high temperature, mechanical damage, and pathogenic infection [17,18,19,20,21,22,23]. In addition, there is a great deal of definite evidence indicating that the regulation of plant development and metabolism also requires WRKYs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the WRKY gene plays an important role in strawberry disease resistance. According to previous research, we know that FaWRKY1 is related to strawberry C. acutatum [ 34 , 35 ], and that FvWRKY42 is a positive regulator of the resistance of wild strawberries against powdery mildew [ 37 ]. In 2016, 59 WRKY genes at different stages of fruit development were found in forest strawberry by transcriptome sequencing [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The separated strains were cultured in a culture medium with potato dextrose agar at 20 °C and a photoperiod of 16/8. Before the strains were inoculated in the strawberries, we cultured them in a medium with strawberry agar (500 g/L of ground strawberries and 1.5% of bacterial agar) to enhance their invasiveness [ 35 ]. Mycelia were scraped from the surface of the strains after 2 weeks of culturing, and conidia suspension was prepared in sterile distilled water with 0.03% ( v/v ) of Tween-80 at a concentration of 10 6 spores per milliliter.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations